Proyecto de ampliación de cobertura en la entrega de valija postal para la ciudad de quito: caso empresa xl worldwide. - Rodríguez Galiano, Teresa Del Rocío (2009)
This project aims to evaluate the possible alternatives which will help grow the company XL WORLDWIDE within the country, in the current demand for this service on routes Guayaquil - Quito, Quito - Guayaquil. Those alternatives are: Alliance Padilla Company SA, a new subsidiary in the capital and sublease service Currier, these alternatives are analyzed and developed in depth in order to select the best option for the company based XL WORLDWIDE financial analysis, market and new opportunities which give higher returns in order to improve service and reduce costs. Thus the actual situation and future performance will be evaluated of the company XL WORLDWIDE, to determine the economic benefits this project provides us. This project in turn discusses possible new markets and new ways to improve the postal service nationwide with the goal of being a leading and well maintained in the competitive level of the others.